THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE, ATTITUDES, AND ACTIONS WITH THE BEHAVIOR OF CHECKING THE DENTAL AND ORAL HEALTH OF PREGNANT WOMEN - Andi Istiqamah; Isnur Hatta; Ika Kusuma Wardani (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: The number of dental and oral health the Indonesian is 57.6%, which is dominated by women (58.5%), especially women of productive age. During pregnancy, there are physical changes, hormonal changes, and behavioral changes, resulting in the changes for the maintenance of dental and oral hygiene. It becomes worse due to an increase in the estrogen and progesteronehormones. Purpose: To analyze the relationship between the level of knowledge, attitudes, and actions with the behavior of checking the dental and oral health of pregnant women. Methods: This study used an analytical observation with a cross-sectional research design. The samples of the study were calculated using the sample size correlation formula. The population in this study were all pregnant women from December 2020 to May 2021,at the Tana Lili Health Center, North Luwu Regency and the samples used were 34 respondents. Results: 70% of pregnant women have a sufficient level of knowledge, 79% of pregnant women have a quite good attitude, 68% of pregnant women have bad actions, and 85% of pregnant women have less behavior. The Spearman correlation test showed a significant relationship between the level of knowledge and the behavior of checking the oral health of pregnant women (p = 0.003), and the strength of the correlation was moderate (r = 0.497). There was a significant relationship between attitudes and behavior of checking the dental and oral health of pregnant women (p=0.023), and the strength of the correlation was low (r=0.390). The sig value for the relationship between action and behavior was (p = 0.009) meaning that there was a significant relationship between the action and the behavior of checking the dental and oral health of pregnant women with a value (r = 0.439) meaning that the correlation strength was moderate. Conclusion: There is a significant relationship between the level of knowledge, attitudes, and actions and the behavior of checking the dental and oral health of pregnant women. Keywords: Action, Attitude, Behavior of checking the dental and oral health, Knowledge